The current status of the Turkish textile and apparel sector's innovation system - Girgin, Aslı Balçak; Ulcay, Yusuf (İdris Karagöz, 2024)
Each sector needs a unique innovation ecosystem and set of policies. Furthermore, we can see that different countries' innovation systems in the same sector are structured differently. This is a critical determinant of how much added value the sector generates. In this context, the first step in optimizing our country's textile and apparel sectoral innovation systems is to assess the current R&D and innovation level and structure. R&D and innovation data for the Turkish textile and apparel industries were revealed for this purpose. The sector's actors and their positioning in the current system were investigated. The data was compared to that of the EU, and inferences were made.

Tüm sektörler farklı bir inovasyon ekosistemine ve farklı politikalara ihtiyaç duyar. Bunun yanında değişik ülkelerde aynı sektöre ait inovasyon sistemlerinin farklı şekillerde yapılanmış olduğunu gözlemleyebiliriz. Bu durum sektörün ne kadar katma değer ürettiğini belirleyen önemli bir unsurdur. Bu kapsamda ülkemizde tekstil ve konfeksiyon sektörel inovasyon sistemlerinin en optimum şekilde yapılandırılmasında ilk adım, mevcut Ar-Ge ve inovasyon düzeyi ve yapılanmasını analiz etmektir. Bu amaçla, bu çalışmada Türk tekstil ve konfeksiyon sektörüne yönelik Ar-Ge ve inovasyon verileri ortaya koyulmuş, sektöre ait aktörler ve bu aktörlerin mevcut sistem içerisinde konumlanması incelenmiştir. Ortaya konan veriler AB’deki veriler ile karşılaştırılarak çıkarımlarda bulunmuştur.
Türk tekstil ve hazır giyim sektörü inovasyon sisteminin güncel durumu
Keywords: Textile Science; Tekstil Bilimi